The Future of Educational Management with AI Chatbots - Labbaf, Neda; Sabeti Choubdar, Leili; Javad Joorabchi, Mohammad; Darvish Motevalli, Mohammad Hossein; Darabani , Sayed Ali (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2024)
Objective: This study aims to explore the potential of AI chatbots in educational management, focusing on their benefits, challenges, and implications for educational institutions.Methods and Materials: The study employs a qualitative research design, using semi-structured interviews to collect data from 21 educational professionals, including administrators, teachers, and technology integration specialists. The participants were selected based on their experience and involvement in educational management and technology integration. Data were analyzed using NVivo software, following coding and thematic analysis to identify key themes and patterns.Findings: The findings reveal three main themes: challenges in educational management, potential benefits of AI chatbots, and concerns regarding their implementation. Key challenges include administrative burden, communication inefficiencies, student support limitations, resource allocation issues, and technology integration difficulties. Potential benefits identified are improved efficiency, enhanced communication, personalized student support, data-driven decision making, and increased accessibility and inclusivity. However, concerns such as privacy and security, dependence on technology, ethical considerations, resistance to adoption, implementation costs, quality of AI interactions, and the need for continuous improvement were also highlighted.Conclusion: AI chatbots hold significant promise for transforming educational management by streamlining administrative processes, enhancing communication, and providing personalized support. However, addressing privacy, security, ethical, and practical challenges is crucial for their successful integration.